Planejamento otimizado da produção de madeira no fomento florestal - Ferreira, Matheus Andrade (2016)
Forest outgrower is a partnership between rural industries and producers to expand their forest base without immobilize capital in purchasing land, and at the same time brings income to farmers. The aim of this study was to develop a mathematical model to optimize the distribution of future forest outgrower areas to be contracted and / or renewal of existing contracts, minimizing the cost of wood delivered to the factory. The forest outgrower areas are distributed throughout the Espírito Santo, south of Bahia and Minas Gerais. Redistribution of these areas is essential to ensure the company's competitiveness at the global pulp market, due to the current economic crisis in Brazil and possible climate change. The mathematical model aimed to reduce the cost of wood at the factory, considering a medium-term planning horizon (tactical). However, due to the need for integration between the strategic and tactical levels, future forestfostering production targets were used as guidelines established by longterm planning. Complementarily were added acreage restrictions available in the municipality, for the conduct of forest forestering contracts. In addition, restrictions on maximum capacity timber storage for deposit and capacity in hiring areas were generated in the scope of the problem. Were created scenarios and were evaluated by the total cost of the objective function, average cost per cubic meter of wood, average transport distance, model processing time and feasibility of implementation of the procurement plan, following the guidance of the company's managers. The mathematical model has shown its efficiency, effectiveness and flexibility in generating scenarios to assist company managers in decision making, in which the scenario 6 was chosen as the best scenario with wood a cost of R$143,01/m³. In addition to proposing alternatives such as pricing of different wood according to the city's location and form homogeneous blocks of promotion/renovation of forest outgrower around the factory.